2013
DOI: 10.2147/opth.s43695
|View full text |Cite
|
Sign up to set email alerts
|

Infectious endotheliitis: a rare case of presumed mycotic origin

Abstract: PurposeTo report an interesting case of infectious endotheliitis of presumed mycotic origin.MethodsA case report of a 56-year-old male farmer who sought medical attention after a month-long evolution of irritative symptoms in his right eye, accompanied by visual acuity (VA) impairment. The patient received topical and oral broad-spectrum antibiotic treatment with no improvement before being referred to a cornea specialist, where he was found to have VA of 20/150 and was noted on biomicroscopy to have endotheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In 2012, Garg [85] noted several fungal etiologies that infect the corneal epithelium which, if left untreated, have the potential to extend into the endothelium and cause decompensation and inflammation. In 2013, Zapata et al [86] reported a case of infectious endotheliitis of suspected mycotic origin. Although no organisms were isolated, clinical improvement was seen after 5 days of antimycotic therapy.…”
Section: Other Causesmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2012, Garg [85] noted several fungal etiologies that infect the corneal epithelium which, if left untreated, have the potential to extend into the endothelium and cause decompensation and inflammation. In 2013, Zapata et al [86] reported a case of infectious endotheliitis of suspected mycotic origin. Although no organisms were isolated, clinical improvement was seen after 5 days of antimycotic therapy.…”
Section: Other Causesmentioning
confidence: 99%
“…If neither viral PCR nor bacterial culture return positive, further etiologies must be investigated. Fungal culture and/or a trial of antimycotic treatment may be warranted [86]. In vivo confocal microscopy can reveal KP and other lesions that might suggest another cause [111].…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation